THE WTO'S INFLUENCE ON THE GLOBAL ECONOMY AND MODERN BUSINESS DYNAMICS - Radojević, Tijana; Rajin, Danica; Nikolić, Jelena; Yildirim, Semil (The European Journal of Applied Economics, 2025)
Established in 1995 as the successor to the General Agreement on Tariffs and Trade (GATT), the World Trade Organization (WTO) is a pivotal institution overseeing international trade. With 166 member countries accounting for over 98% of global trade, the WTO’s primary mission is to facilitate free and fair trade by reducing trade barriers and resolving disputes. It plays a critical role in ensuring adherence to trade rules, particularly in safeguarding the interests of smaller nations, and addresses a wide range of issues including intellectual property and agriculture. Despite its contributions, the WTO faces significant challenges such as adapting to the digital economy, addressing climate change, and countering rising protectionism. Critics argue that its framework often benefits developed nations at the expense of developing countries, underscoring the need for reform. To remain effective and equitable, the WTO must modernize its processes and policies. This paper examines the WTO’s role in regulating international trade, explores the contemporary challenges it faces, and evaluates potential reforms aimed at enhancing its relevance and ensuring fairness for all member states.
Keywords: international trade, international relations, WTO, global market, multilateral trading system